Social mixing patterns relevant to infectious diseases spread by close contact in urban Blantyre, Malawi - Deus Thindwa; Kondwani C. Jambo; John Ojal; Peter MacPherson; Mphatso Dennis Phiri; Amy Pinsent; McEwen Khundi; Lingstone Chiume; Katherine E. Gallagher; Robert S. Heyderman; Elizabeth L. Corbett; Neil French; et al. (Epidemics, 2022)
Introduction: Understanding human mixing patterns relevant to infectious diseases spread through close contact is vital for modelling transmission dynamics and optimisation of disease control strategies. Mixing patterns in low-income countries like Malawi are not well known. Methodology: We conducted a social mixing survey in urban Blantyre, Malawi between April and July 2021 (between the 2nd and 3rd wave of COVID-19 infections). Participants living in densely-populated neighbourhoods were randomly sampled and, if they consented, reported their physical and non-physical contacts within and outside homes lasting at least 5 min during the previous day. Age-specific mixing rates were calculated, and a negative binomial mixed effects model was used to estimate determinants of contact behaviour. Results: Of 1201 individuals enroled, 702 (58.5%) were female, the median age was 15 years (interquartile range [IQR] 5–32) and 127 (10.6%) were HIV-positive. On average, participants reported 10.3 contacts per day (range: 1–25). Mixing patterns were highly age-assortative, particularly those within the community and with skin-to-skin contact. Adults aged 20–49 y reported the most contacts (median:11, IQR: 8–15) of all age groups; 38% (95%CI: 16–63) more than infants (median: 8, IQR: 5–10), who had the least contacts. Household contact frequency increased by 3% (95%CI: 2–5) per additional household member. Unemployed participants had 15% (95%CI: 9–21) fewer contacts than other adults. Among long range (>30 m away from home) contacts, secondary school children had the largest median contact distance from home (257 m, IQR 78–761). HIV-positive status in adults >=18 years-old was not associated with changed contact patterns (rate ratio: 1.01, 95%CI: (0.91–1.12)). During this period of relatively low COVID-19 incidence in Malawi, 301 (25.1%) individuals stated that they had limited their contact with others due to COVID-19 precautions; however, their reported contacts were 8% (95%CI: 1–13) higher. Conclusion: In urban Malawi, contact rates, are high and age-assortative, with little reported behavioural change due to either HIV-status or COVID-19 circulation. This highlights the limits of contact-restriction-based mitigation strategies in such settings and the need for pandemic preparedness to better understand how contact reductions can be enabled and motivated.